Sulfur-doped starch-based hard carbon material, preparation method and application thereof, and sodium ion battery
Through two-stage preoxidation treatment and sulfur doping technology, sulfur-doped starch-based hard carbon material with excellent electrochemical performance was prepared, which solved the problem of low sodium storage capacity of sodium ion battery negative electrode materials and low first-time Coulomb efficiency, achieving both high-efficiency sodium storage and high electrochemical performance.
Patent Information
- Application Number
- CN202411900353.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The low sodium storage capacity of existing sodium ion battery anode materials and low first-time Coulomb efficiency limit their commercial applications.
The active hydroxyl group of starch is regulated by two-stage preoxidation treatment and provides sodium storage active sites through sulfur doping to prepare sulfur-doped starch-based hard carbon material. The material retains the spherical structure and pore structure of the starch during the high-temperature carbonization process, improving electrochemical properties.
The efficient sodium storage performance of hard carbon materials was achieved. The first Coulomb efficiency reached about 90%, and the reversible capacity reached 346.8 mAh g-1, which significantly improved the electrochemical performance of sodium ion batteries.
Smart Images

Figure CN119637849A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of negative electrode materials for sodium ion batteries, and specifically relates to a sulfur-doped starch-based hard carbon material, a preparation method and application thereof, and a sodium ion battery. Background Art
[0002] Sodium-ion batteries are considered to be one of the most competitive candidates for grid-scale energy storage devices due to their economic advantages and excellent electrochemical performance. However, the development of anode materials has severely restricted their commercial application. To date, a large number of anode materials for sodium-ion batteries have been intensively studied. Graphite, as the most successful commercial anode for lithium-ion batteries, is unable to form stable intercalation compounds with sodium ions and its relatively narrow interlayer spacing (<0.37 nm) results in low sodium storage capacity of graphite. In contrast, hard carbon, a complex microstructure consisting of pores, defects, and graphite crystallites, has great commercialization potential due to its abundant resources, low cost, and high capacity.
[0003] Biomass-based hard carbon materials have been widely studied. Biomass materials have the characteristics of wide sources, sustainable regeneration, low pollution and low price. Starch, as the second largest renewable resource on earth, has the advantages of high purity, low cost and natural spherical structure. However, starch releases a large amount of gas during the direct carbonization process. The release of these gases may make the hard carbon structure difficult to control, and usually cannot be directly carbonized to obtain high-performance hard carbon materials.
[0004] The use of pretreatment technology to change the hydroxyl groups at the ends of starch molecules to form a cross-linked structure inhibits the foaming of starch during carbonization, which is of great significance for optimizing the pore structure and electrochemical properties of starch-based hard carbon. Summary of the invention
[0005] In view of the problems existing in the prior art, the purpose of the present invention is to provide a sulfur-doped starch-based hard carbon material and a preparation method and application thereof. In the preparation method, the starch can be stabilized by the first stage of pre-oxidation and the molecular ends of the cross-linked structure can be formed by changing the hydroxyl groups; in the second stage of pre-oxidation, the hydroxyl groups on the ring structure can be converted into aldehydes through oxidation treatment, thereby effectively adjusting the hydroxyl content in the starch. In addition, sulfur doping provides more active sites for sodium ion storage, and the obtained hard carbon material has excellent electrochemical properties, with an initial coulombic efficiency of about 90% and a reversible capacity of 346.8 mAhg. -1 .
[0006] In order to achieve the above invention objectives, the present invention is implemented by the following technical solutions: A method for preparing a sulfur-doped starch-based hard carbon material comprises the following steps: S1: placing the starch material in an air atmosphere for low-temperature pre-oxidation treatment, and cooling it to room temperature to obtain a first precursor; S2: subjecting the first precursor of S1 to a second stage of high-temperature pre-oxidation in an air atmosphere, and cooling to room temperature to obtain a second precursor; S3: mixing the second precursor obtained in S2 and the sulfur source in proportion, ball milling, and then sieving; S4: The precursor powder after sieving S3 is carbonized at high temperature in an inert atmosphere to obtain a hard carbon material with abundant sodium storage sites.
[0007] Preferably, the starch raw material described in S1 is one or more of potato starch, corn starch, bean starch, cereal starch, and wheat starch.
[0008] Preferably, the temperature of the low-temperature pre-oxidation treatment in S1 is 180°C-220°C (specifically 180°C, 190°C, 200°C, 210°C, 220°C, etc.), the insulation time is 3-24 h (specifically 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, etc.), and the cooling method is natural cooling.
[0009] Preferably, in S2, the temperature of the second stage high-temperature pre-oxidation is 230°C~280°C, specifically 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, etc.), the insulation time is 3~12 h (specifically 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.), and the cooling method is natural cooling.
[0010] Preferably, in S3, the sulfur source is any one or more of thiourea, sulfide polyacrylonitrile, and sublimed sulfur; more preferably sublimated sulfur; the mass ratio of the second precursor to the sulfur source is 1:0.5~2 (specifically 1:0.5, 1:1, 1:1.5, 1:2, etc.), the speed range of the ball mill is 100~300 r / min, the ball milling time is 0.1~1 h, and after ball milling, it is sieved through a 300 mesh sieve.
[0011] Preferably, the S4 is specifically: the selected inert atmosphere is nitrogen or argon; more preferably nitrogen. The temperature of high temperature carbonization is 1000-1500°C (specifically 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, etc.), the holding time is 2-6 h (specifically 2h, 3h, 4h, 5h, 6h, etc.), the heating rate is 0.5-5°C / min (specifically 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc.), and the cooling method is natural cooling.
[0012] Furthermore, the present application also protects the sulfur-doped starch-based hard carbon material obtained by any of the above method steps or a combination of the steps. The material has excellent electrochemical properties, with a first coulombic efficiency of about 90% and a reversible capacity of 346.8 mAh g -1 .
[0013] Furthermore, the present application also protects the use of the sulfur-doped starch-based hard carbon material obtained above in the negative electrode of a sodium ion battery.
[0014] Finally, the present application also protects a sodium ion battery, which contains the sulfur-doped starch-based hard carbon material prepared by the above method.
[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) The raw materials required are abundant, low-cost, widely available and sustainably renewable.
[0016] (II) The present invention regulates the active hydroxyl groups of starch through two-stage pre-oxidation treatment, and sulfur doping provides additional sodium storage active sites; the foaming of starch during carbonization is suppressed, and the hard carbon after carbonization not only retains the spherical structure and relatively consistent particle size of starch, but also promotes the formation of closed pores. In addition, sulfur doping provides more sodium storage active sites. The problems of low specific capacity and low first coulomb efficiency of hard carbon in the prior art are overcome.
[0017] (III) Compared with the existing technology, the starch-based hard carbon material has good electrochemical performance. When used as the negative electrode of sodium ion batteries and assembled into button-type half-cells, it has a first coulombic efficiency of about 90% and a capacity of 310 mAh g -1 The above reversible specific capacity.
[0018] (iv) Compared with the traditional biomass hard carbon production process, the preparation process of the present invention does not require chemical processes such as acid and alkali treatment. The preparation method is simple and efficient and suitable for large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1The first cycle charge and discharge performance diagram of the hard carbon negative electrode material prepared in Example 1 and Example 5; Figure 2 This is a rate performance diagram of the hard carbon negative electrode material prepared in Example 1. DETAILED DESCRIPTION
[0020] The present invention is further described below in conjunction with embodiments, which are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, other embodiments obtained by ordinary technicians in the field without creative work are all within the scope of protection of the present invention.
[0021] In the present application, % not specifically indicated indicates the mass percentage, i.e., wt%; the reagents or instruments used without indicating the manufacturer are conventional products that can be purchased commercially.
[0022] Embodiment 1: This embodiment provides a method for preparing a sulfur-doped starch-based hard carbon material, comprising the following steps: S1: 60 g of corn starch was placed in a muffle furnace and kept at 210 °C for 12 h in an air atmosphere. After natural cooling, the first precursor was obtained. S2: placing the first precursor obtained after step S1 in a muffle furnace, heat-treating at 250° C. for 6 h in an air atmosphere, and obtaining a second precursor after natural cooling; S3: 10 g of the second precursor of S2 and 10 g of sulfur powder were mixed in a ball mill at a speed of 200 r / min for 0.5 h to obtain a precursor powder, which was sieved through a 300-mesh sieve; S4: Under a nitrogen atmosphere, the precursor powder sieved from S3 was carbonized at high temperature, heated to 1300°C at a heating rate of 5°C / min, kept warm for 3 h, and cooled naturally to obtain a sulfur-doped starch-based hard carbon material, i.e., a sodium-based hard carbon negative electrode material.
[0023] Example 2 This embodiment provides a method for preparing a sulfur-doped starch-based hard carbon material, comprising the following steps: S1: 60 g of corn starch was placed in a muffle furnace and kept at 210 °C for 12 h in an air atmosphere. After natural cooling, the first precursor was obtained. S2: 10 g of the first precursor of S1 and 10 g of sulfur powder were mixed in a ball mill at a speed of 200 r / min for 0.5 h to obtain a precursor powder, which was passed through a 300-mesh sieve; S3: In a nitrogen atmosphere, the precursor powder of S2 after screening was carbonized at high temperature, and the temperature was raised to 1300°C at a heating rate of 5°C / min, and kept at this temperature for 3 h. The cooling method was natural cooling to obtain the sodium battery hard carbon negative electrode material.
[0024] Example 3 This embodiment provides a method for preparing a sulfur-doped starch-based hard carbon material, comprising the following steps: S1: 60 g of corn starch was placed in a muffle furnace and kept at 210 °C for 12 h in an air atmosphere. After natural cooling, the first precursor was obtained. S2: placing the first precursor obtained after step S1 in a muffle furnace, heat-treating at 250° C. for 3 h, and obtaining a second precursor after natural cooling; S3: 10 g of the second precursor of S2 and 10 g of sulfur powder were mixed in a ball mill at a speed of 200 r / min for 0.5 h to obtain a precursor powder, which was sieved through a 300-mesh sieve; S4: In a nitrogen atmosphere, the precursor powder of S3 after sieving was carbonized at high temperature, and the temperature was increased to 1300°C at a heating rate of 5°C / min, and kept at this temperature for 3 h. The cooling method was natural cooling to obtain the sodium battery hard carbon negative electrode material.
[0025] Example 4 This embodiment provides a method for preparing a sulfur-doped starch-based hard carbon material, comprising the following steps: S1: 60 g of corn starch was placed in a muffle furnace and kept at 210 °C for 12 h in an air atmosphere. After natural cooling, the first precursor was obtained. S2: placing the first precursor obtained after step S1 in a muffle furnace, heat-treating at 250° C. for 12 h in an air atmosphere, and obtaining a second precursor after natural cooling; S3: 10 g of the second precursor of S2 and 10 g of sulfur powder were mixed in a ball mill at a speed of 200 r / min for 0.5 h to obtain a precursor powder, which was sieved through a 300-mesh sieve; S4: In a nitrogen atmosphere, the precursor powder of S3 after sieving was carbonized at high temperature, and the temperature was increased to 1300°C at a heating rate of 5°C / min, and kept at this temperature for 3 h. The cooling method was natural cooling to obtain the sodium battery hard carbon negative electrode material. Example 5 This embodiment provides a method for preparing a starch-based hard carbon material, comprising the following steps: S1: 60 g of corn starch was placed in a muffle furnace and kept at 250 °C for 12 h in an air atmosphere. After natural cooling, the first precursor was obtained. S2: placing the first precursor obtained after step S1 in a muffle furnace, heat-treating at 210° C. for 6 h in an air atmosphere, and obtaining a second precursor after natural cooling; S3: The second precursor obtained in S2 is crushed by ball mill at a ball mill speed of 200 r / min for 0.5 h to obtain precursor powder, which is passed through a 300-mesh sieve; S4: In a nitrogen atmosphere, the precursor powder of S3 after sieving was carbonized at high temperature, and the temperature was increased to 1300°C at a heating rate of 5°C / min, and kept at this temperature for 3 h. The cooling method was natural cooling to obtain the sodium battery hard carbon negative electrode material.
[0026] Example 6 This embodiment provides a method for preparing a sulfur-doped starch-based hard carbon material, comprising the following steps: S1: Place corn starch in a muffle furnace, keep it at 250 °C for 6 h in an air atmosphere, and obtain the first precursor after natural cooling; S2: 10 g of the first precursor of S1 and 10 g of sulfur powder were mixed in a ball mill at a speed of 200 r / min for 0.5 h to obtain a precursor powder, which was passed through a 300-mesh sieve; S3: In a nitrogen atmosphere, the precursor powder of S2 after screening was carbonized at high temperature, and the temperature was raised to 1300°C at a heating rate of 5°C / min, and kept at this temperature for 3 h. The cooling method was natural cooling to obtain the sodium battery hard carbon negative electrode material.
[0027] Example 7 This embodiment provides a method for preparing a sulfur-doped starch-based hard carbon material, comprising the following steps: S1: 60 g of potato starch was placed in a muffle furnace, kept at 210 °C for 12 h in an air atmosphere, and then naturally cooled to obtain the first precursor; S2: placing the first precursor obtained after step S1 in a muffle furnace, heat-treating at 250° C. for 6 h in an air atmosphere, and obtaining a second precursor after natural cooling; S3: 10 g of the second precursor of S2 and 10 g of sulfur powder were mixed in a ball mill at a speed of 200 r / min for 0.5 h to obtain a precursor powder, which was sieved through a 300-mesh sieve; S4: In a nitrogen atmosphere, the precursor powder of S3 after sieving was carbonized at high temperature, and the temperature was increased to 1300°C at a heating rate of 5°C / min, and kept at this temperature for 3 h. The cooling method was natural cooling to obtain the sodium battery hard carbon negative electrode material.
[0028] Example 8 This embodiment provides a method for preparing a sulfur-doped starch-based hard carbon material, comprising the following steps: S1: 60 g of corn starch was placed in a muffle furnace and kept at 210 °C for 12 h in an air atmosphere. After natural cooling, the first precursor was obtained. S2: placing the first precursor obtained after step S1 in a muffle furnace, heat-treating at 250° C. for 6 h in an air atmosphere, and obtaining a second precursor after natural cooling; S3: 10 g of the second precursor of S2 and 10 g of sulfur powder were mixed in a ball mill at a speed of 200 r / min for 0.5 h to obtain a precursor powder, which was sieved through a 300-mesh sieve; S4: In a nitrogen atmosphere, the precursor powder of S3 after sieving was carbonized at high temperature, and the temperature was increased to 1100°C at a heating rate of 5°C / min, and kept at this temperature for 3 h. The cooling method was natural cooling to obtain the sodium battery hard carbon negative electrode material.
[0029] Example 9 This embodiment provides a method for preparing a sulfur-doped starch-based hard carbon material, comprising the following steps: S1: 60 g of corn starch was placed in a muffle furnace and kept at 210 °C for 12 h in an air atmosphere. After natural cooling, the first precursor was obtained. S2: placing the first precursor obtained after step S1 in a muffle furnace, heat-treating at 250° C. for 6 h in an air atmosphere, and obtaining a second precursor after natural cooling; S3: 10 g of the second precursor of S2 and 10 g of sulfur powder were mixed in a ball mill at a speed of 200 r / min for 0.5 h to obtain a precursor powder, which was sieved through a 300-mesh sieve; S4: In a nitrogen atmosphere, the precursor powder of S3 after screening was carbonized at high temperature, and the temperature was raised to 1500°C at a heating rate of 5°C / min, and kept at this temperature for 3 h. The cooling method was natural cooling to obtain the sodium battery hard carbon negative electrode material.
[0030] Example 10 This embodiment provides a method for preparing a sulfur-doped starch-based hard carbon material, comprising the following steps: S1: Mix 10 g corn starch and 10 g sulfur powder in a ball mill at a speed of 200 r / min for 0.5 h to obtain a precursor powder, which is then sieved through a 300-mesh sieve; S4: In a nitrogen atmosphere, the precursor powder of S3 after sieving was carbonized at high temperature, the temperature was increased to 1300°C at a heating rate of 5°C / min, and the temperature was kept for 3 h. The cooling method was natural cooling to obtain the material.
[0031] Embodiment 11 This embodiment provides a method for preparing a sulfur-doped starch-based hard carbon material, comprising the following steps: S1: In a nitrogen atmosphere, 10 g of corn starch was carbonized at high temperature, heated to 1300 °C at a heating rate of 5 °C / min, kept at this temperature for 3 h, and cooled naturally.
[0032] S2: Pass through a 300-mesh sieve to obtain the material.
[0033] The materials obtained in Examples 1-11 were subjected to sodium ion battery assembly and electrochemical testing as follows: Hard carbon material, conductive carbon black, carboxymethyl cellulose and styrene-butadiene rubber were weighed according to the mass ratio of 93.5%:1.5%:2%:3%, and an appropriate amount of deionized water was added. The mixture was stirred to a uniform slurry. The slurry was evenly coated on the surface of the aluminum foil using a 100 μm scraper and dried in a forced air drying oven at 70°C for 12 h. The aluminum foil with active materials was cut into disc-shaped negative electrode sheets, which were then transferred to a glove box for standby use.
[0034] The battery was assembled in a glove box filled with argon atmosphere, using the prepared hard carbon material electrode as the negative electrode and the commercial electrolyte 1.0 mol / L NaPF 6 / EC:DMC(1:1)(V:V) was used as the electrolyte, Na metal sheet was used as the counter electrode, and glass fiber GF / A was used as the separator to assemble the CR2032 button cell.
[0035] The electrochemical performance of the prepared sodium ion half-cell was tested. Specifically, the voltage range was 0.001-2.5 V and the charge flow rate was 0.1C (30 mA g -1 ) at a current density of 1.5 mAh g -1 ) and first charge specific capacity (mAh g -1 ), and calculate the first coulombic efficiency.
[0036] The parameter comparison of the above different embodiments is summarized as follows (Table 1): Table 1. Parameter comparison of different embodiments
[0037] Example 1 is the experimental group, and Examples 2 and 6 are the control groups. The effects of two-stage pre-oxidation treatment and one-stage pre-oxidation treatment on the electrochemical properties of corn starch-based hard carbon were investigated. The two-stage pre-oxidation treatment intensified the cross-linking reaction between corn starch and oxygen, and promoted the formation of closed pores in the process of converting starch into hard carbon. The hard carbon material provided by Example 1 has the best performance. On the basis of its first coulombic efficiency of about 90%, its first charge specific capacity reaches 346.8 mAh g -1The first coulombic efficiency of the hard carbon materials provided in Examples 2 and 6 was 87.6% and 86.8% respectively, and the first charge specific capacity was 311.3 mAh g -1 and 318.2 mAh g -1 .
[0038] Examples 1, 3, and 4 investigated the effects of different pre-oxidation treatment times. In the case of a shorter pre-oxidation time, the hydroxyl groups of corn starch were not completely cross-linked with air, while the longer pre-oxidation time may have destroyed the structure of the pyranose ring of corn starch. The first coulombic efficiencies of the hard carbon materials provided by Examples 3 and 4 were 84.3% and 86.9%, respectively, and the first charge specific capacity was 328.4 mAhg -1 and 321.6 mAh g -1 .
[0039] Example 5 investigates the electrochemical performance of corn starch-based hard carbon without sulfur doping. The first coulombic efficiency of the hard carbon material provided in Example 5 is 88.4%, and the first charge specific capacity is 321.7 mAh g -1 .
[0040] In Example 7, corn starch was replaced with potato starch, and the hard carbon material provided had a first coulombic efficiency of 88.5% and a first charge specific capacity of 337.5 mAh g -1 . Examples 1, 8, and 9 investigated the effects of different carbonization temperatures on the electrochemical properties of starch-based hard carbon. Lower temperatures were not conducive to the formation of closed pores in hard carbon, while higher temperatures would destroy the reversible defect sites on the surface of hard carbon. The first coulombic efficiencies of the hard carbon materials provided by Examples 8 and 9 were 85.4% and 89.2%, respectively, and the first charge specific capacity was 339.7 mAh g -1 and 334.6mAh g -1 .
[0041] Examples 1 and 10 investigated the effect of non-pre-oxidation treatment on the performance of corn starch-based hard carbon. The hard carbon material provided in Example 10 had a first coulombic efficiency of 81.4% and a first charge specific capacity of 295.9 mAh g -1 .
[0042] Example 11 explores the electrochemical performance of direct carbonization of corn starch. The low first coulombic efficiency is mainly attributed to the excessive foaming of corn starch during the carbonization process, which leads to an increase in specific surface area. The first coulombic efficiency of the hard carbon material provided is 78.6%, and the first charge specific capacity is 269.3 mAh g -1 . Although the main inventive examples that affect the factors of this experiment have been described and listed, ordinary persons in the art can understand that various changes, explorations, modifications and combinations can be made to the embodiments without departing from the principles and purpose of the invention, and the scope of the invention is defined by the claims and their equivalents.
[0043] The above basic examples of the present invention and their further selected examples can be freely combined to form multiple embodiments, all of which are embodiments that can be adopted and claimed by the present invention. In the scheme of the present invention, each selected example can be arbitrarily combined with any other basic example and selected example. Those skilled in the art will know that there are many combinations.
[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a sulfur-doped starch-based hard carbon material, characterized in that The following steps are involved: S1: placing the starch material in an air atmosphere for low-temperature pre-oxidation treatment, and naturally cooling it to room temperature to obtain a first precursor; S2: subjecting the first precursor obtained in S1 to a second stage of high-temperature pre-oxidation in an air atmosphere, and naturally cooling to room temperature to obtain a second precursor; S3: mixing the second precursor obtained in S2 and the sulfur source in proportion, ball milling, and then sieving; S4: The precursor powder after sieving S3 is carbonized at high temperature in an inert atmosphere to obtain a sulfur-doped starch-based hard carbon material having abundant sodium storage sites.
2. The preparation method according to claim 1, characterized in that: The starch material in S1 is a mixture of any one or more of potato starch, corn starch, bean starch, cereal starch and wheat starch.
3. The preparation method according to claim 1, characterized in that: The temperature of the low-temperature pre-oxidation treatment in S1 is 180℃~220℃, and the time is 3~24 h.
4. The preparation method according to claim 1, characterized in that: The temperature of the second stage high temperature pre-oxidation in S2 is 230℃~280℃, and the time is 3~12 h.
5. The preparation method according to claim 1, characterized in that: In S3, the rotation speed of the ball mill is 100 to 300 r / min, and the ball milling time is 0.1 to 1 h.
6. The preparation method according to claim 1, characterized in that: In S3, the sulfur source is a mixture of any one or more of thiourea, sulfide polyacrylonitrile, and sublimed sulfur; the mass ratio of the second precursor to the sulfur source is 1:0.5-2; and after ball milling, the product is sieved through a 300-mesh sieve.
7. The preparation method according to claim 1, characterized in that: The inert atmosphere in S4 is nitrogen or argon; the heating rate during high-temperature carbonization is 0.5-5°C / min, the temperature of high-temperature carbonization is 1000-1500°C, and the time is 2-6 h.
8. The sulfur-doped starch-based hard carbon material prepared according to any one of claims 1 to 7.
9. Use of the sulfur-doped starch-based hard carbon material according to claim 8 in a negative electrode of a sodium ion battery.
10. A sodium ion battery, characterized in that: Contains the sulfur-doped starch-based hard carbon material according to claim 8.
Citation Information
Patent Citations
Starch-based carbon fiber and preparation method thereof
CN107502999A
Negative electrode material, preparation method thereof and sodium ion battery
CN117352727A
Starch-based spherical hard carbon negative electrode material, preparation method thereof and battery
CN118183689A
Asphalt-based sodium ion battery negative electrode material and preparation method thereof
CN118289736A
Starch-based hard carbon material as well as preparation method and application thereof
CN118306977A
Cited By
Method for preparing porous carbon material from aldose-saccharide compound, porous carbon material and application
CN120057893A
High-tap-density hard carbon material as well as preparation method and application thereof
CN122166753A